Pengaruh Peer, Financial Literacy Dan Inklusi Keuangan Terhadap Saving Behavior Dengan Motif Sebagai Variabel Intervening (E-BISNIS: JURNAL ILMIAH EKONOMI DAN BISNIS, 2025)
This research aims to examine and analyze the influence of peers, financial literacy, and financial inclusion on saving behavior with saving motives as an intervening variable. This research is a quantitative study with a descriptive approach. The population in this study consists of all KIP Kuliah scholarship recipient students at Slamet Riyadi University Surakarta. The sampling technique used purposive sampling method using the Slovin formula. The sample in this study consists of KIP Kuliah scholarship recipient students at Slamet Riyadi University Surakarta with the provision that the respondents concerned are in accordance with the author's criteria. The sample in this study amounted to 85 respondents. The data collection method used questionnaires distributed directly. The data used in the research is primary data collected through questionnaire surveys. Data analysis used multiple linear regression analysis and path analysis. The research results show: 1) Peers (X1), Financial literacy (X2), Financial Inclusion (X3) and Saving Motives (Z) have a positive and significant effect on Saving behavior, 2) Peers (X1), Financial literacy (X2), Financial Inclusion (X3) have a positive and significant effect on Saving Motives. 3) Financial literacy (X2) and Financial Inclusion (X3) have a positive and significant effect on Saving behavior mediated by Saving Motives. 4) Saving Motives are unable to mediate the influence of Peers on Saving Behavior.